Analysis of Financial Inclusion and Sustainability of Women's MSMEs - Putri Asrina; Rahmita Budiarti Ningsih; Anthony Mayes; Indri Yovita (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The existence of women-owned MSMEs makes a significant contribution to improving the local economy and community welfare. However, in managing MSMEs, women entrepreneurs also face challenges in supporting business sustainability, both internal and external challenges. This study aims to analyze the relationship between financial inclusion and the sustainability of micro, small, and medium enterprises (MSMEs) managed by women in Pekanbaru City. This research was conducted using a quantitative approach by providing questionnaires to respondents. The sampling technique used purposive sampling. The data analysis technique used was Partial Least Square (PLS). The test results show that digital literacy has a direct influence on financial inclusion, while government support, financial literacy, and education have a direct influence on the sustainability of women's MSMEs in Pekanbaru City. Furthermore, it was also found that there was no indirect influence moderated by the financial inclusion variable. So financial inclusion is not a variable that is able to connect financial literacy, digital literacy, education and government support for the sustainability of women's MSMEs in Pekanbaru City.